Beyond Sustainability: Paradigms for Complexity and Resilience in the Built Environment - Simona Mannucci (Urban Science, 2025)
Conventional approaches in architecture and urban planning still rest on modernist, deterministic assumptions that downplay the nonlinearity and deep uncertainty that characterize contemporary cities. Sustainability, although crucial, has often been operationalized through incremental, efficiency-oriented checklists that struggle to address systemic transformation. This conceptual theory synthesis reframes the built environment as a complex adaptive system and interrogates three paradigms that have arisen in the wake of the sustainability turn: resilience planning, adaptive planning, and regenerative design. Drawing on an integrative, narrative review of interdisciplinary scholarship, the article maps these paradigms onto a functional “what–how–why” theoretical scaffold: resilience specifies what socio-technical capacities must be safeguarded or allowed to transform; adaptive planning sets out how planners can steer under conditions of deep uncertainty through sign-posted, flexible pathways; and regenerative design articulates why interventions should move beyond mitigation toward net-positive socio-ecological outcomes. This synthesis positions each paradigm along an uncertainty spectrum and identifies their complementary contributions.